Evaluation of a serologic method for the detection antibodies against Brucella canis (Veterinary Science, 2017)
Taking into account that there are diverse methods for the antibodies serologic determination against Brucella canis, and that the majority of these methods are imprecise in terms of the detection of true positive, it is that we focus present work toward the evaluation of the rapid plate agglutination test (RSAT), in comparation with the agar gel inmunodiffusion test (AGID). Such studies were carried out with the aim of obtaining their sensibility, specificity and predictive value. We should keep in mind that although the sample animals are not a big amount, the results obtained comparing this test with the standard gold allowed us to obtain a relative sensibility of 100%, a relative specificity of 96.23% and a positive predictive value of 66.66%.
Keywords: Rapid slide agglutinaiton test (RSAT); Brucella canis; Sensibility; Specificity